Characterizing the seismogenic zone of a major plate boundary subduction thrust: Hikurangi Margin, New Zealand - Wallace, Laura M.; Reyners, Martin; Cochran, Ursula; Bannister, Stephen; Barnes, Philip M.; Berryman, Kelvin; Downes, Gaye; Eberhart-Phillips, Donna; Fagereng, Ake; Ellis, Susan; Nicol, Andrew; McCaffrey, Robert; et al. (Geochemistry, geophysics, geosystems : G3, 2009)
The Hikurangi subduction margin, New Zealand, has not experienced any significant (>Mw 7.2) subduction interface earthquakes since historical records began ∼170 years ago. Geological data in parts of the North Island provide evidence for possible prehistoric great subduction earthquakes. Determining the seismogenic potential of the subduction interface, and possible resulting tsunami, is critical for estimating seismic hazard in the North Island of New Zealand. Despite the lack of confirmed historical interface events, recent geodetic and seismological results reveal that a large area of the interface is interseismically coupled, along which stress could be released in great earthquakes. We review existing geophysical and geological data in order to characterize the seismogenic zone of the Hikurangi subduction interface. Deep interseismic coupling of the southern portion of the Hikurangi interface is well defined by interpretation of GPS velocities, the locations of slow slip events, and the hypocenters of moderate to large historical earthquakes. Interseismic coupling is shallower on the northern and central portion of the Hikurangi subduction thrust. The spatial extent of the likely seismogenic zone at the Hikurangi margin cannot be easily explained by one or two simple parameters. Instead, a complex interplay between upper and lower plate structure, subducting sediment, thermal effects, regional tectonic stress regime, and fluid pressures probably controls the extent of the subduction thrust's seismogenic zone.